Posterior Glottic Stenosis with a Calcified Interarytenoid Scar Band: CT and Laryngoscopic Correlation - Liu, B.P.; Bové, M.J.; Nemeth, A.J. (American Journal of Neuroradiology, 2010)
SUMMARY: A 52-year-old man with burn injuries and prolonged intubation developed PGS with hoarseness, dyspnea, and bilateral vocal cord immobility. On CT, a calcified interarytenoid scar band was identified, corresponding to an interarytenoid scar on laryngoscopy. Endoscopic laser lysis of the calcified scar band relieved the symptoms. We present laryngoscopic and CT findings of PGS with interarytenoid calcification along with the postlysis findings. The classification, clinical findings, imaging, and management of PGS are reviewed. PGSposterior glottic stenosisVPvocal processes